Global seagrass carbon stock variability and emissions from seagrass loss - Krause, Johannes R.; Cameron, Clint; Arias-Ortiz, Ariane; Cifuentes Jara, Miguel; y otros más (Springer, 2025)
Seagrass ecosystems are recognized for their capacity to sequester and store organic carbon, but there is large variability in soil organic carbon stocks associated with plant traits and environmental conditions, making the quantification and scaling of carbon storage and fluxes needed to contribute to climate change mitigation highly challenging. Here, we provide estimates of carbon stocks associated with seagrass systems (biomass and soil) through analyses of a comprehensive global database including 2700+ seagrass soil cores. The median global soil Corg stock estimate is 24.2 (12.4 – 44.9) Mg Corg ha−1 in the top 30 cm of soil, 27% lower than estimates from previous global syntheses, refining the IPCC Tier 1 soil Corg stock currently used for carbon accounting in places without local data. We estimate that seagrass carbon stocks at risk of degradation could emit 1,154 Tg (665 – 1699) CO2 with a social cost of $213 billion (2020 US dollars), if no action is taken to conserve these habitats.